2016
DOI: 10.1021/acs.iecr.6b02234
|View full text |Cite
|
Sign up to set email alerts
|

Correlation for Calculating Heat Transfer Coefficient in Conical Spouted Beds

Abstract: A correlation has been proposed for predicting local bed-to-surface heat transfer coefficients in conical spouted beds based on an experimental study conducted using beds made up of sand, sawdust, and their mixtures under various operating conditions, namely, different static bed heights and gas velocities over minimum spouting. A comparison of the results with those obtained using the correlations in the literature proved that they provide very poor predictions and, furthermore, they are not able to predict l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 28 publications
2
13
0
Order By: Relevance
“…Our results coincided with previous findings; for example, Saldarriaga et al [34] found an HHV of 19.43 MJ/kg for U. europaeus. We found high HHVs for all functional parts, very similar to those of pine sawdust, which is one of the most commonly used biomasses for thermal processes worldwide [39,[41][42][43]. In general, the volatile matter of both species was very high while the ash content was very low, which, according to Vassilev et al [41], is important because where there is a higher volatile content in a thermal process, the yield of biomass includes light hydrocarbons, CO, CO 2 , H 2 , moisture and tars.…”
Section: Discussionsupporting
confidence: 53%
“…Our results coincided with previous findings; for example, Saldarriaga et al [34] found an HHV of 19.43 MJ/kg for U. europaeus. We found high HHVs for all functional parts, very similar to those of pine sawdust, which is one of the most commonly used biomasses for thermal processes worldwide [39,[41][42][43]. In general, the volatile matter of both species was very high while the ash content was very low, which, according to Vassilev et al [41], is important because where there is a higher volatile content in a thermal process, the yield of biomass includes light hydrocarbons, CO, CO 2 , H 2 , moisture and tars.…”
Section: Discussionsupporting
confidence: 53%
“…Following the unsatisfactory agreement between the correlations available in literature to describe the local heat transfer coefficients in SB reactors (mandatory for the correct design of drying processes), a new expression was obtained by Saldarriaga et al [252] using a bed of sand and sawdust inside a conical SB reactor. The model was found valid for the definition of the most adequate position of heat transfer devices within the annulus of the reactor.…”
Section: Plant Scale Modellingmentioning
confidence: 99%
“…This procedure continues until all of the significant regressors are inserted into the correlation. Figure 7 shows the flow diagram of the algorithm written in Scilab, which has been adapted from that by Saldarriaga et al 50,51 The methodology described for regression analysis has been applied to eqs 1−6. Overall, this strategy improved the fit quality of the correlations for predicting the capacity curves of the microhydrocyclones studied in this paper, but acceptable fit levels were not attained.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Given that the fit quality of the correlations in the literature is not suitable, modifications in their proportionality and/or exponential coefficients should be tried to improve their predictions. To that end, a methodology has been used based on that established by Saldarriaga et al , for proposing correlations for the minimum operational velocity and heat-transfer coefficients in conical spouted beds. This methodology is based on the combination of multivariate regression and optimization techniques for the stepwise minimization of the residual error according to significance tests applied to the coefficients.…”
Section: Resultsmentioning
confidence: 99%